The Meaning of Struggle and Struggle Meaning: The Contribution of Nahdlatul Ulama in Building Indonesianness - Alhakim, Bambang Amir (Sospol, 2026)
This article examines the contribution of Nahdlatul Ulama (NU) in building the solidity of the Unitary State of the Republic of Indonesia (NKRI) through the process of social construction of meaning. This study uses the sociological approach of Max Weber's meaning and the social construction theory of Peter Berger & Thomas Luckmann as a framework of analysis to understand how NU transforms the struggle for independence into a form of worship (the meaning of struggle), while constantly fighting for the legitimacy of the Republic of Indonesia as a sacred moral community (the struggle for meaning). The research methods used were ethnography and case studies with data collection through in-depth interviews, participatory observations, focus group discussions, and analysis of historical texts in three strategic regions: East Java, Central Java, and South Kalimantan. The results of the study show that NU has succeeded in integrating traditional Islamic values with the spirit of nationalism through a network of Islamic boarding schools, religious rituals, and collective narratives. The process of objectification, internalization, and legitimacy is carried out systematically, making love of the homeland part of faith. Another important finding is the central role of NU women in reproducing the meaning of nationality at the grassroots level through taklim assemblies, value-based economic practices, and oral traditions. This article concludes that the solidity of the Republic of Indonesia does not only depend on political or military structures, but especially on the durability of social meaning that continues to be reproduced by socio-religious movements such as NU.